Tinjauan Kelengkapan Pengisian Persetujuan Tindakan Kedokteran Pasien Rawat Inap di Rumah Sakit Setia Mitra - Hudiyati Agustini (MEDICORDHIF Jurnal Rekam Medis, 2017)
ABSTRACT The purpose of this research is general to know completeness of filling in Approval of Medical Action form of inpatient at Setia Mitra Hospital. The specific objective is to identify the Standard Operating Procedures (SPO) on completing the Approval of Medical Action form, calculating the completeness of the completion of the Approval of Medical Action form and knowing the factors causing incomplete filling of the inpatient Approval of Medical Action forms at Setia Mitra Hospital. The research method used is descriptive method and the steps that are done is by collecting data, data classification or analysis, then make conclusions and reporting. Also conducted interview method to the head of medical record at Setia Mitra Hospital. From the results of the study, conclusions were concluded at Setia Mitra Hospital, which already had SPO filling out the Approval of Medical Action and there was an attempt to improve it better. Complete patient identification of 81,23% incomplete equal to 18,77%, complete medical treatment 100%, complete authentication 70% and incomplete 30%, complete recording complete 71,79% and an incomplete amount of 28.20%. Overall, the most complete is the important note that is filled 100% type of medical action, while the most incomplete component is complete 30% complete authentication. Factors that led to incompleteness according to the chief medical record interview were that doctors were busy checking patients so that they did not have time to complete the Approval of Medical Action form. Based on the results of this research, the filling out of Approval of Medical Action forms at Setia Mitra Hospital is still not good and needs to be improved. ABSTRAK Tujuan penelitian ini secara umum untuk mengetahui kelengkapan pengisian formulir persetujuan tindakan kedokteranpasien rawat inap di RS Setia Mitra. Tujuan khusus adalah mengidentifikasi standar prosedur operasional (SPO) tentang pengisian formulir persetujuan tindakan kedokteran, menghitung kelengkapan pengisian formulir persetujuan tindakan kedokteran dan mengetahui faktor- faktor yang menyebabkan ketidaklengkapan pengisian formulir persetujuan tindakan kedokteran pasien rawat inap di RS Setia Mitra. Metode penelitian yang digunakan adalah metode deskriptif dan langkah-langkah yang di lakukan adalah dengan pengumpulan data, klasifikasi pengelohan atau analisis data, kemudian membuat kesimpulan dan pelaporan.Juga dilakukan metode wawancara kepada kepala rekam medis di RSSetia Mitra. Dari hasil penelitian diambil kesimpulan di RS Setia Mitra sudah ada SPO pengisian persetujuan tindakan kedoktean dan sudah ada usaha untuk memperbaiki dengan lebih baik. Pengisian identitas pasien yang lengkap sebesar 81,23% yang tidak lengkap sebesar 18,77%, jenis tindakan kedokteran lengkap 100%, autentifikasi yang lengkap sebesar 70% dan yang tidak lengkap sebesar 30%, pencatatan yang baik yang lengkap sebesar 71,79% dan yang tidak lengkap sebesar 28,20%. Secara keseluruhan maka yang paling lengkap adalah catatan penting yaitu diisi 100%jenis tindakan medis, sedangkan komponen yang paling tidak lengkap adalah autetifikasi sebesar 30% yang diisi lengkap.Faktor- faktor yang menyebabkan ketidaklengkapan menurut wawancara kepala rekam medis adalah karena dokter sibuk untuk memeriksa pasien sehingga tidak punya waktu untuk melengkapi formulir persetujuan tindakan kedokteran. Berdasarkan hasil penelitian ini, pengisian formulir persetujuan tindakan kedokteran di RS Setia Mitra masih kurang baik dan perlu diperbaiki.